Aplikasi Teori Isnad Cum Matn Harald Motzki Dalam Hadis Misoginis Penciptaan Perempuan - Faisal Haitomi; Muhammad Syachrofi (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2020)
Harald Motzki is one of the orientalists who study the hadith objectively. One of Motzki's theories in studying hadith is isnad cum matn. This theory is a method in searching the history of hadith and combining aspects of isnad and matan as well as the Common Link theory which was popularized by Juynbol. In this article the author uses misogynistic traditions about the creation of women, bearing in mind that these traditions are often used as a reason to legitimize discrimination against women. The author found that misogynistic traditions about the creation of women were delivered by the Prophet himself, and at the same time, the Prophet also became the common link of these hadiths. In Mysoginy perspectives raditions or more specifically traditions that talk about the creation of women from ribs are also authentic from the Prophet and are delivered in two versions, namely the long version and the short version, which are then recorded in several hadith books.